Controlling the flow balance: In vitro characterization of a pulsatile total artificial heart in preload and afterload sensitivity. Issue 1 (30th July 2021) - Hildebrand, Stephan; Diedrich, Mario; Brockhaus, Moritz; Finocchiaro, Thomas; Cuenca, Elena; De Ben, Heiko; Steinseifer, Ulrich; Schmitz‐Rode, Thomas; Jansen, Sebastian Victor
Abstract: The objective of this study is to identify the preload and afterload sensitivity of the ReinHeart TAH 2.0. For adequate left‐right flow balance, the concept of a reduced right stroke volume (by about 10%) and active adaption of the right diastole duration are evaluated concerning the controllability of the flow balance. This study used an active mock circulation loop to test a wide range of preload and afterload conditions. Preload sensitivity was tested at atrial pressures (APs) between 4 and 20 mm Hg. Left afterload was varied in a range of 60‐140 mm Hg mean aortic pressure (MAP), right afterload was simulated between 15 and 40 mm Hg. Four scenarios were developed to verify that the flow difference fully covers the defined target range of 0‐1.5 L/min. Although a positive correlation between inlet pressure and flow is identified for the right pump chamber, the left pump chamber already fills completely at an inlet pressure of 8‐10 mm Hg. With increasing afterload, both the left and right flow decrease. A positive flow balance (left flow exceeds right flow) is achieved over the full range of tested afterloads. At high APs, the flow difference is limited to a maximum of 0.7 L/min. The controllability of flow balance was successfully evaluated in four scenarios, revealing that a positive flow difference can be achieved over the full range of MAPs. Under physiological test conditions, the linear relationship between flow and heart rate was confirmed, ensuring good controllability of the TAH. Abstract : This study identifies the preload and afterload sensitivity of the downsized total artificial heart ReinHeart TAH 2.0. The concept of a reduced right stroke volume and the active adaption of right diastole duration are investigated over the full range of TAH's parameter setting to achieve a positive flow difference. The controllability of the flow balance was successfully evaluated in four scenarios.